Analisis Kepuasan Pelanggan Perusahaan Galangan Kapal dengan Customer Satisfaction Index untuk Strategi Pemasaran Berbasis SWOT - Febriana Putri Wahyono, Qhintara; Waluyo, Minto (Fakultas Teknik UMRI, 2024)
The shipbuilding industry plays a crucial role in Indonesia's economy. Customer satisfaction is a key factor in the success of shipbuilding companies to remain competitive in both domestic and global markets. This study aims to analyze customer satisfaction levels using the Customer Satisfaction Index (CSI) method and to develop a marketing strategy based on SWOT analysis. The CSI calculation indicates a customer satisfaction level of 67.42%, categorized as